Testing critical point universality along the l - line - Nissen, J. A.; Swanson, D. R.; Lipa, Z. K. Geng,J. A.; Dohm, V.; Israelsson, U. E.; DiPirro, M. J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
We are currently building a prototype for anew test of critical-point universality at the lambda transition in 4He, which is to be performed in microgravity conditions. The flight experiment will measure the second-sound velocity as a function of temperature at pressure from 1 to 30 bars in the region close to the lambda line. The critical exponents and other parameters characterizing the behavior of the superfluid density will be determined from the measurements. The microgravity measurements will be quite extensive, probably taking 30 days to complete. In additional to the superfluid density, some measurements of the specific heat will be made using the low-g simulator at the Jet Propulsion Laboratory. The results of the superfluid density and specific heat measurements will be used to compare the asymptotic exponents and other universal aspects of the superfluid density with the theoretical predictions currently established by renormalization group techniques.